Primaeval History Interpreted : The Rewriting of Genesis 1-11 in the Book of Jubilees - Ruiten, J.T.A.G.M. van (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
This volume deals with the primaeval history in the Book of Jubilees, an interpretative rewriting of the biblical narratives of Genesis through Exodus 19, written in the second century BCE. It contains a close comparison of Genesis 1-11 and Jubilees 2-10, in order to get a clear picture of the specific way the biblical story was rewritten. Each chapter offers an overall comparison of the parallel pericopes in Genesis and Jubilees, with special attention to the structure of the passages. It then gives a synoptic overview of the text of the parallel passages, along with a classification (e.g., addition, omission, variation, rearrangement), and analysis of the dissimilarities. The work is important for those interested in the history of biblical interpretation, in post-biblical Jewish literature and in intertexuality.